EPRDF's revolutionary democracy and religious plurality: Islam and Christianity in post-Derg Ethiopia - Haustein, Jörg; Østebø, Terje (Journal of Eastern African studies, 2012)
In 1991 the Ethiopian Peoples' Revolutionary Democratic Front (EPRDF) introduced policies aimed at recognizing the country's long-standing religious diversity, providing a public arena for religious groups, and maintaining a sharp division between religion and the state. This further eroded the traditionally dominant position of the Ethiopian Orthodox Church, strengthened Protestant Christian and Muslim communities, and created a more fluid and competitive configuration among the religious communities. Seeking to maintain its political power, the EPRDF has at the same time made efforts to monitor and control the different religious communities. Therefore, the last 20 years have been marked by uneven developments, in which the government's accommodating attitudes have been interlaced with efforts to curtail the influence of the religious communities. This article surveys the intersection and reciprocal influences between EPRDF policies and religious communities over the last 20 years, and discusses how Muslims and Christians (Orthodox and Protestant) have negotiated their roles in relation to politics and public life. These developments have, the article argues, led to the emergence of divergent and competing narratives, reconfiguring self-understanding, political aspirations and views of the religious other. The EPRDF ideology of “revolutionary democracy” has, in this sense, enabled religion to surface as a force for social mobilization and as a point of reference for attempting to define nationhood in Ethiopia.
Gesehen am 23.09.2022